2022
DOI: 10.21098/bemp.v25i1.1619
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal and Monetary Policy Interactions in Indonesia During Periods of Economic Turmoil in the Us: 2001q1-2014q4

Abstract: This study investigates the formation of the interaction between monetary and fiscal policies in Indonesia during periods of economic turmoil in the US (external shock) based on the Hybrid New Keynesian (HNK) model. The study estimates the HNK model using the Full Information Maximum Likelihood and time-series data over theperiod 2001Q1-2014Q4. The result reveals the form of coordination is a monetary-led policy mix between active monetary policy and passive fiscal policy. The degree of coordination is down wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Economic recovery strategies can be implemented through fiscal and monetary stimuli to increase national output (Baldwin and Mauro 2020;Hubbard et al 2014;Iacoviello and Navarro 2019). The central bank can maintain its benchmark interest rate to reduce recessionary pressure through policy coordination and quantitative easing (Utama et al 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Economic recovery strategies can be implemented through fiscal and monetary stimuli to increase national output (Baldwin and Mauro 2020;Hubbard et al 2014;Iacoviello and Navarro 2019). The central bank can maintain its benchmark interest rate to reduce recessionary pressure through policy coordination and quantitative easing (Utama et al 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Governments and monetary authorities worldwide are coordinating policies to restore the economic conditions affected by external shocks. Most previous studies in many countries have indicated that coordination is better than isolation (Baldwin and Mauro 2020;Utama et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation